The Football Association Medical Research Programme: an audit of injuries in professional football: an analysis of ankle sprains - Woods, C (BMJ Group, 2003)
Aim: To conduct a detailed analysis of ankle sprains sustained in English professional football over two competitive seasons. Methods: Club medical staff at 91 professional football clubs annotated player injuries. A specific injury audit questionnaire was used together with a weekly form that documented each club's current injury status. Results: Completed injury records for the two competitive seasons were obtained from 87% and 76% of the participating clubs. Ankle ligament sprains accounted for 11% of the total injuries over the two seasons, with over three quarters (77%) of sprains involving the lateral ligament complex. A total of 12 138 days and 2033 matches were missed because of ankle sprains. More sprains were caused by contact mechanisms than non-contact mechanisms (59% v 39%) except in goalkeepers who sustained more non-contact sprains (21% v 79%, p<0.01). Ankle sprains were most often observed during tackles (54%). More ankle sprains were sustained in matches than in training (66% v 33%), with nearly half (48%) observed during the last third of each half of matches. A total of 44% of sprains occurred during the first three months of the season. A high number of players (32%) who sustained ankle sprains were wearing some form of external support. The recurrence rate for ankle sprains was 9% (see methodology for definition of reinjury). Conclusion: Ankle ligament sprains are common in football usually involving the lateral ligament complex. The high rate of occurrence and recurrence indicates that prevention is of paramount importance.